Imaging of large coronary fistula using echocardiography - Özkan Candan; Çetin Geçmen; Müslüm Şahin; Ahmet Güner; Sabahattin Gündüz (KARE Publishing, 2018)
Coronary fistulas are defined as the presence of an abnormal connection between the coronary arteries and the low-pressure vascular area or the cardiac cavity. The clinical significance depends on the amount of blood flow through the fistula segment, the volumetric load on the right and left heart chambers, and whether it leads to a coronary steal phenomenon. Although fistula flow can be better visualized by angiographic methods, it can also be seen by echocardiography. In this case, the fistula flow draining to the left ventricle was demonstratively visualized.